Adapting Language Tests to Hybrid Learning: EFL Teachers’ Challenges and Their - Fitriani Fitriani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
The objective of this study is to explore teachers’ challenges in conducting test in hybrid setting as well as their practices in the context of ELT classroom. The teachers also provide the solutions to overcome the problems. This is qualitative research that employs a case study as the approach. The data are obtained through questionnaires and semi-structured interviews with 8 English teachers of senior high school. The results highlight a number of major issues emerged in conducting tests with the combination of face-to-face and online classroom (hybrid setting) such as: (1) constructing level of thinking test; (2) integrating technology; (3) monitoring students; (4) assessing students fairly; (5) and inadequate facilities. Therefore, this study is a reflection on assessment in hybrid learning which suggests the administrators and authorities of education policy evaluate the guidelines to enhance quality of sustained assessment for students in hybrid learning model.